2017
DOI: 10.4236/as.2017.85029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2,4-D-Choline Based Herbicide Systems in 2,4-D Tolerant Soybean (<i>Glycine max</i> L.)

Abstract: Weeds are the most limiting factor in soybean production in South Carolina. With early emergence and rapid growth, weeds effectlively compete for water, nutrients, and light resources. The recent evolution of herbicide resistant weeds has made it increasingly difficult for growers to effectively control weeds in soybean. Glyphosate and ALS-resistant Palmer amaranth biotypes have spread rapidly throughout South Carolina, especially in areas where resistance management is lacking. Soybean varieties have been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…which was similar to what was observed by Joseph et al [20] during the same study period. Data were presented separately by year if a significant treatment by year interaction was observed.…”
Section: D Joseph Et Al American Journal Of Plant Sciencessupporting
confidence: 93%
See 1 more Smart Citation
“…which was similar to what was observed by Joseph et al [20] during the same study period. Data were presented separately by year if a significant treatment by year interaction was observed.…”
Section: D Joseph Et Al American Journal Of Plant Sciencessupporting
confidence: 93%
“…Visual soybean injury was less than 5% for all treatments and studies (data not shown). The total rainfall received at the study sites in 2012 and 2013 was 680 mm and 647 mm, respectively [20]. Similar to studies conducted by Joseph et al [20], rainfall was also lower in June and July of 2012 compared to the same period in 2013 at the study sites.…”
Section: D Joseph Et Al American Journal Of Plant Sciencessupporting
confidence: 83%
“…a Agricultural Sciences (TRT 2 -6) that included 2,4-D choline at POST1 provided 94% to 99% control of pitted morningglory; however, in treatments without 2,4-D choline (TRT 7 -9), control declined to 85% to 89% for 2012 (Table 4). In a similar study, Merchant [21] found that the control of pitted morningglory increased when an auxinic herbicide was mixed with glufosinate rather than sprayed alone. At 2 WAP2, control of pitted morningglory was greater than 90% in 2012 with all treatments (TRT 2 -6) containing 2,4-D choline and glyphosate combinations (Table 4).…”
Section: Pitted Morningglory Controlmentioning
confidence: 89%